Anticipating Vehicle Traffic Increase on Improved Inter-Urban Roads : Evidence from Three Decades of Transport Projects in Developing Regions - Stokenberga, Aiga; Ogita, Satoshi (Taylor and Francis, 2021)
Consideration of the traffic generated by inter-urban road investments is important for assessing their economic feasibility and external costs and for designing sustainable road maintenance strategies. While the literature and evidence on generated traffic is growing, it has almost exclusively focused on advanced economies. In contrast, readily available methodologies for predicting the generated traffic impacts are lacking in low and middle income countries (LMICs), where most of the future road investments will be made and where detailed travel demand models and data that would be needed to feed them are often not available. This study attempts to fill this gap by specifically focusing on observed traffic growth and its drivers in developing countries. After reviewing the literature on generated traffic modelling, it presents empirical evidence on the characteristics and outcomes of inter-urban road projects implemented over the last three decades across 68 LMICs. The study quantifies the statistical association between, on the one hand, the travel time or vehicle operating cost (VOC) savings resulting from the road improvement and, on the other hand, the observed short-term growth in traffic on the project roads. Controlling for a range of macro-economic and project-level attributes, both travel time savings and VOC reductions are found to have a statistically significant, positive association with observed short-term traffic growth of a magnitude that much exceeds the elasticities reported in developed country literature. Population growth in the project country/State/province during the project implementation period is also found to have a large, positive association with traffic growth, while per capita income growth is found to have a marginal effect. Toll roads (albeit representing a small share of the sample) are found to have statistically significantly lower observed traffic growth compared to non-toll roads even after controlling for the other project characteristics.